Dinamika Konsentrasi Oksigen Terlarut Akibat Limbah Cair Domestik di Hulu Sungai Citarum Menggunakan Model Dinamik - Fanny Novia; Laila Febrina (Jurnal Dampak, 2018)
High pollutant load from municipal discharges around the upstream of Citarum River contributes to the water quality problems of the river. Dynamic modelling was developed to analyze the behaviour of dissolved oxygen in upper of Citarum river using STELLA® as a tool. The modelling area consist of four segments namely Wangisagara, Jembatan Koyod, after Cisirung WWTP and Nanjung. Calibration and validation was done to get the most approaching simulated data to actual data. Average Mean Error (AME) and Average Variation Error (AVE) for all segments was 1.65% and 5.8%, therefore the developed model was valid. Sensitivity analysis shown that the dynamic of dissolved oxygen in upper of Citarum river was most affected by BOD load from municipal sources, decay coefficient of BOD (Kd), maximum rate of photosynthesis (pm) and fractional duration of daylight (f).